Hybridization Histochemistry of Neural Transcripts. Issue 1 (8th April 2016) - Young, W. Scott; Song, June; Mezey, Éva
Abstract: Expression of genes is manifested by the production of RNA transcripts within cells. Hybridization histochemistry (or in situ hybridization) permits localization of these transcripts with cellular resolution or better. Furthermore, the relative amounts of transcripts detected in different tissues or in the same tissues in different states (e.g., physiological or developmental) may be quantified. This unit describes hybridization histochemical techniques using either oligodeoxynucleotide probes (see Basic Protocols 1 and 2, Alternate Protocol 1) or RNA probes (riboprobes; see Basic Protocols 3 and 5). These methods include a more recent approach using commercially available sets of oligodeoxynucleotide pairs for colorimetric and fluorescent detection (see Basic Protocol 2), as well as a method for detection of the Y chromosome using either mouse or human riboprobes (see Basic Protocol 5). Additional methods include colorimetric detection (see Basic Protocol 4) and tyramide signal amplification (TSA) of digoxigenin‐labeled probes (see Alternate Protocol 2), and autoradiographic detection of radiolabeled probes (see Basic Protocol 6). Finally, methods are provided for labeling oligodeoxynucleotide (see Support Protocol 1) and RNA (see Support Protocol 2) probes, and verifying the probes by northern analysis (see Support Protocol 3). © 2016 by John Wiley & Sons, Inc.